(3cJGH GdaJhgs ((3GdSjO SdjeGf s)
(3ChdgG (B:s
(3EjGc EjGc Cf JXgQ YdjgG ZjQ CgdgG hdG JefYhG CgdgG efgG s
(3BNQgG (B:s
(3hfYhP HGddg ef GdRjGOI hGdfbUGf hGdZdW hGdfSjGf Efg cQje efGf QMje QMef JeJ GdaJhg HMeO Gddg hYhfg hMSf Jhajbg s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
Keywords: (3Gdafhf GdMQHjI h GdaQhSjIs